Seasonal changes influence the improvement in asthma symptoms by exercise training in subjects with asthma**. (3rd June 2019) - Mendes, Felipe A. R.; França-Pinto, Andrezza; Martins, Milton A.; Cukier, Alberto; Stelmach, Rafael; Giavina-Bianchi, Pedro; Carvalho, Celso R. F.
Abstract: Objective : To investigate whether patients with moderate-to-severe asthma who commence an exercise training program in winter or summer show differences in exercise capacity, health-related quality of life (HRQoL) and asthma symptoms. Methods : Forty-two consecutive subjects visiting the outpatient clinic were enrolled in the 17-week rehabilitation program. One group of patients received the intervention from summer to winter (SWG, n = 21), and the other group participated from winter to summer (WSG, n = 21). Before and after the exercise training program, all patients were evaluated by cardiopulmonary exercise test, pulmonary function test, quality of life questionnaire and a daily diary that evaluated clinical asthma symptoms. Results : After the training period, both groups improved similarly in health-related quality of life (HRQoL) and aerobic capacity. The WSG patients had a greater increase that those in the SWG in asthma symptom-free days ( p < 0.05). Conclusions : Our results indicate that seasonal variations affect the improvement in asthma symptoms after an exercise training program but have no effect on health-related quality of life, exercise capacity or pulmonary function.